2015
DOI: 10.1007/s12072-015-9676-3
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous recanalization for hepatic vein-type Budd-Chiari syndrome: long-term patency and survival

Abstract: Percutaneous recanalization can provide good long-term patency and survival in HV-type BCS patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 20 publications
2
44
1
Order By: Relevance
“…Recent studies from Asia have shown the effectiveness of percutaneous recanalization in various BCS patients and the survival rates in these patients were comparable to that of a European population undergoing TIPS and orthotopic liver transplantation. 4,[15][16][17][18][19][20][21] In our study we achieved technical success of 91.7% for HV pattern, 100% for IVC pattern and 88.8% for combined HV and IVC pattern of BCS. Clinical success was achieved in 79.2% of patients.…”
Section: Discussionsupporting
confidence: 50%
“…Recent studies from Asia have shown the effectiveness of percutaneous recanalization in various BCS patients and the survival rates in these patients were comparable to that of a European population undergoing TIPS and orthotopic liver transplantation. 4,[15][16][17][18][19][20][21] In our study we achieved technical success of 91.7% for HV pattern, 100% for IVC pattern and 88.8% for combined HV and IVC pattern of BCS. Clinical success was achieved in 79.2% of patients.…”
Section: Discussionsupporting
confidence: 50%
“…HVC‐BCS patients have undergone percutaneous recanalisation more frequently as compared to classical BCS patients . Several studies have shown good long‐term efficacy and survival‐benefit of this procedure (Table ) …”
Section: Radiological Interventionmentioning
confidence: 99%
“…Angioplasty has been extensively used in Asia with good long‐term outcomes (Table ) . Han et al published their experience in 168 Chinese BCS patients undergoing successful percutaneous angioplasty with median follow‐up of 30 months .…”
Section: Radiological Interventionmentioning
confidence: 99%
“…Tracheal stent has been widely used clinically for the treatment of tracheal fistula [4][5][6][7] or tracheal stenosis [8][9][10][11][12][13]. However, tracheal stents placement may bring a series of complications, and stent removal sometimes is necessary [23].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, some patients may not be willing to undergo open surgery considering that they are too weak or sick under this circumstance [2]. Since first adoption of self-expanding metal stents to treat bronchial obstruction in 1989 [3], the efficacy and safety of tracheal stent has been proven for the treatment of tracheal fistula [4][5][6][7] or tracheal stenosis [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%